Losing brain networks during death - Han Li; Yunting Xiang; Taicheng Huang; Ruojia Ren; Huichun Luo; Yi Zhang; Jin‐Jun Ding; Jie Weng; Xiao‐Na Zhu; Yonglan Du; Xiao Li; Yimeng Liu; et al. (Interdisciplinary Medicine, 2025)
Abstract Death represents the end of all living organisms. The pattern of brain activity disappearance following death, however, has not been fully elucidated. Here we investigated brain activity dynamics following cardiac arrest using ultra‐high field 11.7 T magnetic resonance imaging (MRI) in longitudinal approach and multi‐modal analyses. Initially, the functional connectivity (FC) analysis revealed a non‐linear trajectory of whole‐brain network disassembly. Subsequently, through dynamic FC analysis, we identified two discrete FC patterns in the whole brain that showed opposite changes from life to death, representing the dissipation process of local brain function specificity. In addition, the default mode network (DMN), sensorimotor network (SMN), and interoceptive network (IN) were identified during the live stage by independent component analysis. However, results of dynamic functional network connectivity analysis showed that SMN and IN preferentially disappeared after cardiopulmonary arrest, which is the critical turning point of death. Notably, the surviving DMN showed a decreased spatial map but stronger FC with the right dorsolateral thalamus, retrosplenial cortex, and corpus callosum during the near‐death stage. This suggests that DMN may be the final regulator of systemic brain shutdown. This study aims to address the limited understanding of brain function changes during death from an imaging perspective and provides inspirations for the definition of death and the inference of death time.